The Development of Learning Materials of Online Probing-Prompting Method at IAIN Antasari in Indonesia - Cahyadi, Ani (Institut Agama Islam Negeri Imam Bonjol Padang, 2017)
The learning materials based on independent learning and constructivism for students especially online probing-prompting method has not been developed yet in the learning process at IAIN Antasari. The purposes of this study are to develop the learning materials of online probing prompting method including the syllabus, lesson units, instructional materials, student assessment sheet, learning media, and online learning design which have been validated by the experts. It is also aimed to identify the quality of the learning materials based on the experts’ assessment. This study used research and development (R D) approach. The finding of the study showed that IAIN Antasari has developed the learning materials of online probing prompting method including the syllabus, lesson units, instructional materials, student assessment sheet, learning media, and online learning design. The study also found that the experts’ assessment on the quality of the learning materials of online probing prompting method at IAIN Antasari was quite good in terms of the feasibility aspects of the materials, presentation, language and images.